Financial Technology Berdasarkan Prinsip Syariah dan Model Penggunaan Akad Dalam Fintech Syariah : Kajian Terhadap Fatwa DSN MUI - Heri Firmansyah; Muhammad Rusydi; Irwan Irwan; Mulyatno Mulyatno (Tabayyanu : Journal Of Islamic Law, 2024)
The rapid development of Financial Technology (fintech) has significantly transformed the global financial system, including the Islamic financial sector. In Indonesia, the emergence of sharia-based fintech reflects the increasing demand for digital financial services that comply with Islamic legal principles. However, the implementation of fintech within the framework of Islamic law raises important juridical issues, particularly regarding the validity and application of contracts (akad) used in digital financial transactions. This study aims to analyze the concept of sharia fintech based on Islamic principles and examine the models of contracts applied in sharia fintech according to the fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This research employs a normative juridical method using a statutory and conceptual approach by analyzing relevant DSN-MUI fatwas, Islamic legal doctrines, and related regulations concerning technology-based financial services. The findings reveal that sharia fintech must operate in accordance with fundamental Islamic principles by avoiding elements of riba (usury), gharar (uncertainty), and maisir (gambling). Furthermore, the study identifies several permissible contracts used in sharia fintech, including al-ba’i, ijarah, mudharabah, musyarakah, wakalah bi al-ujrah, and qardh. These contracts function as the primary legal instruments for ensuring sharia compliance in digital financial transactions. This study contributes to the development of Islamic economic law by providing a juridical analysis of sharia contract implementation in contemporary fintech practices and reinforcing the role of DSN-MUI fatwas as normative legal foundations for digital Islamic finance in Indonesia.